Performance and failure during energy testing of zinc oxide varistor processed from different powder size fraction and passivation thickness - Karim A.N.M.; Begum S.; Hashmi M.S.J. (2023)
The processing of ZnO varistor has a long route with numerous contributing variables. The role of particle size distribution in the starting powder is very crucial in varistor fabrication and performance evaluation. The varistors are also needed to be passivated before the evaluation of electrical performance. It was envisaged that the passivation thickness would influence the failure characteristics during energy testing as heat dissipation would be affected by the thickness. To investigate the above phenomena, the standard as produced varistor powder was fractionated to different narrow distributions containing large, medium and fine particles. Though there was no appreciable difference in physical properties but it was higher for discs fabricated with finer fraction of powder. However, the affect on green strength was quite reverse. In terms of electrical performance, the varistor discs with fine fraction of powder exhibited better properties though the energy absorption capability was poor. The variation of passivation thickness did not influence the energy absorption capability that much but the failure mode was changed. The higher thickness caused the failure by electrical puncture.